2019
DOI: 10.1186/s12957-019-1722-5
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of totally robotic versus robotic-assisted radical distal gastrectomy for advanced gastric cancer: a mono-institution retrospective study

Abstract: PurposeBy comparing short- and long-term outcomes following totally robotic radical distal gastrectomy (TRDG) and robotic-assisted radical distal gastrectomy (RADG), we aimed to assess in which modus operandi patients will benefit more.MethodsFrom January 2015 to May 2019, we included 332 patients undergone RADG (237) and TRDG (95). Based on the propensity score matching (PSM), inclusion and exclusion criteria, 246 patients were finally included in the propensity score-matched cohort including RADG group (164)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…It suggested that early food-taking after C-section could promote the recovery of gastrointestinal function. This result is accorded with the guidelines and several studies about the Enhanced Recovery after Surgery (ERAS) of C-section [17][18][19] [ [17][18][19]. From 2017 to 2019, a research group summarized series of studies, and composed standardized ERAS guidelines (part1-3) for preoperative care in C-section [20][21][22] .…”
Section: Early Oral Feeding (Eof) After C-section Can Promote the Rec...mentioning
confidence: 87%
“…It suggested that early food-taking after C-section could promote the recovery of gastrointestinal function. This result is accorded with the guidelines and several studies about the Enhanced Recovery after Surgery (ERAS) of C-section [17][18][19] [ [17][18][19]. From 2017 to 2019, a research group summarized series of studies, and composed standardized ERAS guidelines (part1-3) for preoperative care in C-section [20][21][22] .…”
Section: Early Oral Feeding (Eof) After C-section Can Promote the Rec...mentioning
confidence: 87%
“…This finding could be attributed to the advanced robotic surgery systems, including an internal EndoWrist with seven degrees of freedom, three-dimensional vision, tremor filter, and short learning curve, which prevented injuries from the blood vessels and allowed precise dissection and high flexibility for surgeons [ 32 ]. Previous studies proved that one critical barrier to the wide RG application in clinical practice was high costs [ 12 , 13 , 16 , 17 , 33 , 34 ]. Our study also found that RADG group had higher medical cost than the LADG group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a robotic surgical system has been introduced to address the limitations of laparoscopy and is welcomed in GC treatment owing to its satisfying early postoperative outcomes [13,[15][16][17]. Robotic gastrectomy (RG) has been confirmed to be a safe and feasible technique with better anatomical and operative conditions and comparable long-term results compared to LG [12,15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The reason was that the ranges of gastrectomy in the two researches were different. Relevant studies have shown no statistically significant difference in the actual time of gastrectomy between robotic surgery system and traditional laparoscopic surgery [ 21 ]. For this reason, the time of surgery was further studied, and no significant difference was found in the dissociation time in vivo of patients between the two groups ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%